Haem-responsive gene transporter enables mobilization of host haem in ticks - J. Perner; T. Hatalova; M. Cabello-Donayre; V. Urbanova; D. Sojka; H. Frantova; D. Hartmann; D. Jirsova; J. M. Pérez-Victoria; P. Kopacek (Open Biology, 2021)
Ticks, notorious blood-feeders and disease-vectors, have lost a part of their genetic complement encoding haem biosynthetic enzymes and are, therefore, dependent on the acquisition and distribution of host haem. Solute carrier protein SLC48A1, aka haem-responsive gene 1 protein (HRG1), has been implicated in haem transport, regulating the availability of intracellular haem. HRG1 transporter has been identified in both free-living and parasitic organisms ranging from unicellular kinetoplastids, nematodes, up to vertebrates. However, an HRG1 homologue in the arthropod lineage has not yet been identified. We have identified a single HRG1 homologue in the midgut transcriptome of the tick Ixodes ricinus, denoted as IrHRG, and have elucidated its role as a haem transporter. Data from haem biosynthesis-deficient yeast growth assays, systemic RNA interference and the evaluation of gallium protoporphyrin IX-mediated toxicity through tick membrane feeding clearly show that IrHRG is the bona fide tetrapyrrole transporter. We argue that during evolution, ticks profited from retaining a functional hrg1 gene in the genome because its protein product facilitates host haem escort from intracellularly digested haemoglobin, rendering haem bioavailable for a haem-dependent network of enzymes.